Steeped in Shame: An Exploration of Family Sexual Socialization Among Black College Women. (December 2020) - Leath, Seanna; Pittman, Jami C.; Grower, Petal; Ward, L. Monique
Most research on Black girls' sexuality emphasizes reducing risk behaviors, with less attention to dimensions of healthy and normative sexual development, such as body positivity. To address this gap, we sought to explore the diversity of sexual messaging young Black women received during their formative years. Using consensual qualitative research methods, we explored how 50 Black college women (ages 18–24 years) described their sexual socialization within family contexts in relation to their current sexual beliefs and behaviors. The following themes emerged from the data: messages of discretion, negative messages about physical appearance, messages of deference, messages of abstinence, absence of sexual messages, messages of body positivity, messages of egalitarianism, messages of sex positivity, and messages of sexual distrust and dismissiveness. Black families' sexual socialization processes were also influenced by ethnicity, social class, and religious orientation. Our findings situate Black women's family sexual socialization practices within a sociohistorical framework and highlight the need to support Black girls' healthy sexual development by eliminating fear, shame, or taboo around sexual exploration. Education and advocacy efforts should focus on communicating openly with youth to help them make more positive decisions about sex and bodily autonomy.